Lateral Closing Wedge Osteotomy for Cubitus Varus: A Case Report - Kandel, Prakriti Raj; Baral, Rajiv; Chitrakar, Niva; Singh, Gyaneshwar Prasad; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2018)
Supracondylar fracture is the most common fracture in children and yet are not treated timely or properly leading to various complications, cubitusvarus being the most common delayed complication1-5. There are various osteotomies that have been proposed for correcting cubitusvarus, but they all have their limitations. In this case study, we have reviewed the functional and cosmetic results of a simple lateral closing wedge osteotomy. A lateral closing wedge osteotomy was done for cubitusvarus of the right elbow of a 17 years old girl following a neglected supracondylar fracture of the right humerus.The carrying angle which was 18⁰ preoperatively became 12⁰ postoperatively following which the patient did not have any difficulty in fully flexing the elbow and could swing her upper limb freely while walking. Closing wedge supracondylar osteotomy is an effective treatment for cubitusvarus both functionally and cosmetically. Journal of Universal College of Medical Sciences (2016) Vol.04 No.02 Issue 14, page: 43-45